Introducing communication theory : analysis and application - West, Richard (New York, NY : McGraw Hill Education, 2018)
As we present the seventh edition of Introducing Communication Theory: Analysis and Application, we remain excited by its enormous success. The previous five editions demonstrate that communication theory courses are vibrant, that teachers of communication understand the importance of theoretical thinking, and that both instructors and students appreciate the consistent and organized template we employ throughout. This text explores the practical, engaging, and relevant ways in which theory pirates in our lives. It is written primarily for students who have little or no background in communication theory.We originally wrote the book because we thought that students eed to know how theorizing helps us understand ourselves, as well as our experiences, relationships, media, environment, and culture. We also wrote this book because we believe that students should have a text that relates theory directly to their lives. We felt that some books insulted the student and trivialized theory while other books were written at a level that was far too advanced for an undergraduate. In this book, we take great care to achieve the following additional objectives
Part One: Foundations -- Communication, Theory and Research -- Part Two: Understanding the Dialogue -- The Self and messages -- Relationship Development -- Groups, teams and organizations -- The Public -- The media -- Culture and Diversity.
Includes bibliographical references and index.
Keywords: COMMUNICATION